Master triathletes have not reached limits in their Ironman triathlon performance. Issue 1 (14th May 2012) - Stiefel, M.; Knechtle, B.; Lepers, R.
<x xml:space="preserve">Abstract</x> The purpose of this study was to analyze the participation and performance trends of male triathletes in the "Ironman Switzerland" from 1995 to 2010. Participation trends of all finishers aged between 18 and 64 years were analyzed over the 16‐year period by considering four 4‐year periods 1995–1998, 1999–2002, 2003–2006, and 2007–2010, respectively. The 3.8‐km swimming, 180‐km cycling, 42‐km running times, and total race times were analyzed for the top 10 triathletes in each age group from 18 to 64 years. The participation of master triathletes (≥40 years old) increased over the years, representing on average 23%, 28%, 37%, and 48% of total male finishers during the four 4‐year periods, respectively. Over the 1995–2010 period, triathletes older than 40 years significantly improved their performance in swimming, cycling, running, and in the total time taken to complete the race. The question whether master Ironman triathletes have yet reached limits in their performance during Ironman triathlon should be raised. Further studies investigating training regimes, competition experience, or socio‐demographic factors are needed to gain better insights into the phenomenon of the relative improvement in ultra‐endurance performance with advancing age.